INDIAN CONSTITUTION: REMINISCING 75 GLORIOUS YEARS OF ITS ADOPTION AND THE WAY FORWARD - Singh, Tongbram Radhabinod; R.K Premila Devi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Adopted on January 26,1950, Indian constitution heralded the beginning of a new era of democracy, liberty, and equality. Over the past 75 years, it has stood as a beacon of justice and resilience, guiding the world’s largest democracy through profound socio-political and economic transformations including that of scheduled Caste, Tribe, OBCs, minorities etc. This living document, rooted in the principle of justice, liberty, equality and fraternity, showcase India’s diverse, inclusive and pluralistic society. Under the visionary leadership of Dr. B.R. Ambedkar, the Constituent Assembly drafted the Constitution that established the framework for governance, fundamental rights, and directive principles, ensuring a balance between individual freedom and collective responsibility. To address evolving needs and challenges, the Constitution has been amended multiple times in the past seven decades. Landmark changes, such as decentralization of power, expansion of fundamental rights, inclusion of socio-economic reforms, have reinforced its adaptability. It has also upheld the sanctity of democracy through its checks and balances and the pivotal role played by the judiciary. The Constitution has guided India through critical events, from integration and reorganization of states, economic liberalization and technological advancement to social justice movements and rising global issues and challenges. Its role in fostering unity, protecting individual rights, and enabling inclusive growth remains unparallel. As the country celebrates 75 years of its Constitution, it is a moment to reflect and recollect on its enduring legacy and recommit to its core values, ensuring it continues to empower every citizen while embracing changes and progress. The Constitution stands not just as a legal framework but as a testament to India’s vision of an equitable and prosperous society.